Role of Education in the Empowerment of Women in India - Harun Al Rasid Mondal (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Education is not only the main pillar of nation-building, but through education, a nation moves towards progress. In a country, with different races of people, both men and women became uplifted towards development when illuminated by education. By the united force of men and women, especially women, a country leads its way to the path of success. Women’s empowerment is a necessity for this success. Again, education is the most powerful instrument of empowerment as it generates consciousness that leads to empowerment. Hence, to pave the way for women’s emancipation and empowerment, education plays a pivotal and inevitable role. According to Pandit Jawaharlal Nehru –"If you teach a male, you educate an individual If you educate a lady, you educate an entire family.” Women who are educated and empowered succeed in society, business, and family life. So, Women empowerment refers to increasing women's social, economic, and educational power. It refers to an environment where there is no gender bias and equal rights in the community, society, and workplaces. Today, according to the GOI report, the male literacy rate is currently at 84%, while the female literacy rate is less than 70%. Again, the most recent labor force surveys conducted by the NSSO (National Sample Survey Office) published the female worker population ratio (%) on a status basis in the country during 2013-14 and 2015-16 are 29.6% and 25.8% respectively. Education helps women become aware of their rights, dignity, and opportunities. It gives them the chance to make a more meaningful decision in terms of political engagement and decision-making choices about life. Thus, education can benefit from building self-confidence, self-efficiency, and decision-making power and increasing gender parity in an organization or institution